PERLINDUNGAN HAK CIPTA ATAS KARYA ARSITEKTUR PERUMAHAN DI INDONESIA - Anita Sinaga, Niru; Rahmat, Diding; Lumban Gaol, Selamat; Zein, Subhan (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
In UUHC it is explained that architectural works are protected objects. However, copyright violations of architectural works still often occur. Therefore, it is interesting and needs to be studied: How is the application of copyright protection for residential architectural works in Indonesia and what obstacles are found in the application of copyright protection for residential architectural works in Indonesia. This study is a normative legal study, using a statute approach, a conceptual approach, and a comparative approach. Using secondary data obtained from primary and secondary legal sources related to laws and regulations and policies on Copyright Protection for Residential Architectural Works in Indonesia. The results of the study show that the Implementation of Copyright Protection for Residential Architecture in Indonesia has not been running well in the sense that violations still often occur. The implementation of Copyright Protection for Residential Architecture in Indonesia is hampered by, among others: lack of socialization of laws and regulations; Lack of legal awareness in society; Lack of good coordination among law enforcers; Weak sanctions given and UUHC is not adequate enough. The solution is: The need to create implementing regulations for the Copyright Law specifically as a complement to the Copyright Law; Cooperate with various related parties and carry out continuous socialization and provide stricter sanctions if violations occur.